The Nile Delta - Negm, Abdelazim M. (Springer, 2017)
This volume presents up-to-date research on the Nile Delta and discusses the challenges involved in and opportunities for improving its productivity. The topics addressed include: groundwater in the Nile Delta and its quality; the mapping of groundwater with remote sensing technologies; land degradation; salt-affected soils; on-farm irrigation; the remediation of agricultural drainage water for sustainable reuse; the use of satellite images to estimate the bathymetry of coastal lakes; the assessment of the Nile Delta coastal zone and its management; its sediment and water quality; and fishing ports, fish and fisheries. The book closes with a review of the latest findings on the Nile Delta and offers conclusions and recommendations for future research to fulfill the requirements for sustainable development. It provides a unique and topical resource for researchers, graduate students and policymakers alike.
Includes index.
Keywords: Groundwater -- Egypt -- Nile River Delta.; Water-supply -- Egypt -- Nile River Delta.; Egypt -- Nile River Delta.; elektronické knihy; electronic books